Digital-Based Social Studies Learning to Improve Social Literacy Students - Depi Fibriyanti; Nuning Christana; Hilyati Milla (CV. Generasi Insan Rafflesia, 2026)
The development of digital technology has had a significant impact on the world of education, including the process of teaching Social Studies. Digital-based Social Studies instruction is one innovation that can improve the quality of learning while supporting the enhancement of students’ social literacy. This study aims to analyze the implementation of digital-based Social Studies instruction in improving students’ social literacy. The research method used is a qualitative approach in the form of a literature review. Data were obtained from various sources, such as scientific journals, books, and articles relevant to digital learning and social literacy. The results indicate that the use of digital media in IPS instruction can improve students’ ability to understand social phenomena, think critically, communicate effectively, and foster a sense of social responsibility. Additionally, digital-based learning creates a more interactive, engaging, and flexible learning environment. However, its implementation still faces several challenges, such as limited technological facilities, low digital literacy, and teachers’ readiness to utilize digital learning media. Therefore, support for infrastructure, teacher training, and innovative learning strategies are needed so that digital-based social studies learning can run optimally and sustainably improve students’ social literacy.